Murabahah Financing in Islamic Banks with Fiduciary Collateral Review from the Perspective of Legal Certainty and Utility - Nugraha, Ivan; Imaniyati, Neni Sri; Putra, Panji Adam Agus (Indonesian Journal of Social Science Research, 2024)
One of the financing contracts offered by Islamic banks is the Murabahah financing contract. The Murabahah financing contract functions to increase the utility of money and capital, as well as the utility of goods. Article 127 of the Compilation of Sharia Economic Law (KHES) allows the seller to request the buyer to provide collateral in the Murabahah contract. Fatwa DSN-MUI No. 03/DSN-MUI/IV/2000 regarding Murabahah permits banks to request collateral from financed customers. This provision aims to ensure that customers are serious about making payments. Based on KHES and the fatwa, banks are allowed to request collateral from customers to protect or ensure that their rights are not violated. In practice, to ensure that customers comply with payments, banks request collateral from customers. This collateral can be movable or immovable property. Collateral in the form of immovable property is called fiduciary collateral. Fiduciary collateral is regulated in Law No. 42 of 1999 concerning Fiduciary Collateral (UUJF). According to Article 5 paragraph 1 of UUJF, the imposition of collateral with fiduciary collateral "must" be made by a notarial deed. With this provision of UUJF, there is a difference. KHES and the fatwa of DSN MUI do not require financing contracts to be made using a notarial deed, while UUJF requires it to be made by a notarial deed. Islamic banks, some of which require financing contracts to be made by a notarial deed, while others do not. The adoption of UUJF in Islamic financing is considered inappropriate because it violates Sharia values. Objectives: (1) Explain the regulations used in Murabahah financing contracts in Islamic banks with fiduciary collateral according to the objectives of legal certainty and utility. (2) Describe the implementation of legal protection for customers using Murabahah financing contracts in Islamic banks with fiduciary collateral according to the objectives of legal certainty and utility. Research Method: Research approach: normative juridical. Research nature: descriptive analysis. Data types: secondary data and primary data. Sample determination technique: purposive sampling. Data collection technique: literature study and interviews. Data analysis technique: interpretation and legal analogy.